Robotnik na wynagrodzeniu w Ml 3,5 jako symbol kryzysu społecznego w i poł. V w. przed Chr. - Zawadzki, Arnold (Verbum Vitae, 2014)
The main aim of the article is to illustrate the social crisis in the 5th century BC, whose symbol in Mal 3,5 is a hireling working for wages. The grammatical and syntactic analysis of the expression Sükar-Säkîr helps to elucidate the situation of the hireling in the 5th century BC brought almost to the status of slave. The editorial addition, identifiable in Mal 3,1-5, is in turn the evidence of attempt to incorporate the original prophecy of Malachi in the process of extinguishing the embers of the social crisis.